2009
DOI: 10.1108/09590550910956241
|View full text |Cite
|
Sign up to set email alerts
|

Indian consumers' purchase behavior toward US versus local brands

Abstract: PurposeThe purpose of this paper is to examine the direct and indirect effects of individuals' self‐concept, product‐oriented variables (i.e. consumer's need for uniqueness (NFU), and clothing interest), and brand‐specific variables (i.e. perceived quality and emotional value) on purchase intention toward a US retail brand versus a local brand that are available in the Indian market.Design/methodology/approachData obtained from 405 college students in India were analyzed using structural equation modeling.Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 56 publications
4
55
0
1
Order By: Relevance
“…Although numerous studies have been conducted on various aspects of fashion clothing brands, very few studies have focused on local fashion clothing brands. Among the notable investigations on local fashion clothing brands, Indian consumers' purchase behavior, brand equity and purchase intention were examined in the context of Indian fashion clothing brands vs US fashion clothing brands (Kumar, Kim and Pelton, 2009;Kumar, Lee and Kim, 2009;Lee et al, 2010). Clothing interest of Indian consumers was found to influence THE emotional value and perceived quality for US fashion clothing brands rather than Indian brands (Kumar, Kim and Pelton, 2009;Kumar, Lee and Kim, 2009), while attitude toward US brands was found to have positive effects on emotional value and perceived quality, whereas it was found to have negative effect in the case of Indian brands (Kumar, Kim and Pelton, 2009;Kumar, Lee and Kim, 2009).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous studies have been conducted on various aspects of fashion clothing brands, very few studies have focused on local fashion clothing brands. Among the notable investigations on local fashion clothing brands, Indian consumers' purchase behavior, brand equity and purchase intention were examined in the context of Indian fashion clothing brands vs US fashion clothing brands (Kumar, Kim and Pelton, 2009;Kumar, Lee and Kim, 2009;Lee et al, 2010). Clothing interest of Indian consumers was found to influence THE emotional value and perceived quality for US fashion clothing brands rather than Indian brands (Kumar, Kim and Pelton, 2009;Kumar, Lee and Kim, 2009), while attitude toward US brands was found to have positive effects on emotional value and perceived quality, whereas it was found to have negative effect in the case of Indian brands (Kumar, Kim and Pelton, 2009;Kumar, Lee and Kim, 2009).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Among the notable investigations on local fashion clothing brands, Indian consumers' purchase behavior, brand equity and purchase intention were examined in the context of Indian fashion clothing brands vs US fashion clothing brands (Kumar, Kim and Pelton, 2009;Kumar, Lee and Kim, 2009;Lee et al, 2010). Clothing interest of Indian consumers was found to influence THE emotional value and perceived quality for US fashion clothing brands rather than Indian brands (Kumar, Kim and Pelton, 2009;Kumar, Lee and Kim, 2009), while attitude toward US brands was found to have positive effects on emotional value and perceived quality, whereas it was found to have negative effect in the case of Indian brands (Kumar, Kim and Pelton, 2009;Kumar, Lee and Kim, 2009). Direct and indirect effects of Indian consumers' need for uniqueness, gender and attitudes toward US fashion clothing brands were found on three dimensions of brand equity: perceived quality, brand loyalty and brand associations with brand awareness, while for Indian fashion clothing brands, these effects are found for just one brand equity dimension: perceived quality (Lee et al, 2010).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Generation Y consumers may be a lucrative market for clothing retailers, especially the branded ones, but research studies on their interest and buying intention of clothing are scant. Kumar, Kim, and Pelton (2009) have suggested that more studies are needed to determine the significant factors in relation to clothing interest and purchase intention.…”
Section: Introductionmentioning
confidence: 99%
“…Tariq and Iqbal [34] found that need for uniqueness is positively associated with intentions to buy a foreign apparel brand. Kumar, Kim and Pelton [32] also found positive association between need for uniqueness and purchase of global brand. Third result indicated that Pakistani consumers' ethnocentrism is negatively associated with intention to buy global brand.…”
Section: Discussionmentioning
confidence: 85%
“…The construct of consumers' need for uniqueness is based on the theory of uniqueness presented by Snyder and Fromkin [30] which expresses individual characteristic to identify one's self image by purchasing material goods [31].Uniqueness Theory describes that consumers seek distinction by adopting diverse behaviors and show undesirability to adopt similar things owned by others. Kumar, Kim and Pelton [32] defined need for uniqueness as a person's desire to be seen as distinguished from others in the society. People wear certain branded apparels to uniquely express their personality and image [33].…”
Section: Need For Uniqueness and Intentions To Buy Global Brandsmentioning
confidence: 99%